2018
DOI: 10.1007/s00167-018-4987-2
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity physical activity increases and sedentary behavior decreases following total knee arthroplasty in patients with osteoarthritis

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
(64 reference statements)
3
25
0
Order By: Relevance
“…Previous studies have shown that moderate to vigorous PA does not change following TKA [19,20,27]. One possibility of promoting activity behavior change may therefore be to promote smaller and more feasible changes in PA by targeting specific intensities of activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that moderate to vigorous PA does not change following TKA [19,20,27]. One possibility of promoting activity behavior change may therefore be to promote smaller and more feasible changes in PA by targeting specific intensities of activity.…”
Section: Discussionmentioning
confidence: 99%
“…This was a substudy of a comprehensive longitudinal observational study. The details of the study protocol have been previously published [35] and results have also been published [27]. Briefly, presurgery assessments were done 2 weeks before TKA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found a postoperative increase of 4903 steps/d in a small group of patients [24]. Frimpong et al [14] demonstrated an increase of 50 minutes spent on light PA. Three other studies found no significant difference in walking time, gait cycles, or accelerometer counts at 6 months [9,12,25]. The small PA increase of 9 minutes after 6 months found in our study is therefore more or less in line with the current literature.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis showed no increase in PA at 6 months and a small-to-moderate increase at 12 months [6]. Finally, Frimpong et al [14] showed an increase in patientreported PA as well as an accelerometer-measured decrease in sedentary behavior (À5.9%) and concomitant increase in light PA (þ5.8%) 6 months after KA.…”
mentioning
confidence: 97%